Identifying the Complexity of the Food-Energy-Water Nexus Based on Emergy Analysis in Crop Production Systems of China - Beibei Guo; Tingting Cheng; Tingting Sun; Yi Tong; Sifeng Nian (Land)
To elucidate the food-energy-water (FEW) nexus, the paper proposes a framework for multifunctional development objectives within the context of CPSs, integrating emergy analysis and the coupled coordination model. The article’s primary focus is on the utilization of blue and green water in the cultivation of a variety of food crops and the acquisition of purchased energy. The paper was evaluated according to three key indicators: stability, development, and sustainability. Furthermore, a quantitative evaluation of the trade-offs among the FEW nexus and its constituent sub-nexuses was conducted over the period from 2000 to 2022. The study revealed that China has witnessed an expansion in its total CPS inputs, with renewable inputs accounting for 32.89% and an average annual input-output ratio of 37.98%. The annual emergy values for food, energy, and water resources were 6.85 × 1023 Sej, 1.43 × 1023 Sej, and 7.91 × 1022 Sej, respectively. The annual growth rates were 2.16%, 2.11%, and 0.77%, respectively. The CPS exhibits an average proportion of green and blue water resources of 64.37% and 35.63%, respectively. The coupling coordination of the FEW nexus demonstrates a transition between years from mild dysfunctional recession to quality coordinated development, with the coordinated use of FEW resources increasing for maize, largely maintained for rice, and decreasing for wheat, soybean, and potato. The objective of this study is to provide differentiated strategies for regional food conservation and sustainable development worldwide.